Semantics-Based Learning Media System Web Basic Mathematics Junior High School - Yowe, Samson Cornelius Gele; Astawa, I Gede Santi; Suhartana, I Ketut Gede; Santiyasa, I Wayan; Dwidasmara, Ida Bagus Gede; Wibawa, I Gede Arta (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 1 (2022): JELIKU Volume 11 No 1, August 2022, 2022)
Mathematics is a very important science because it is related to human life. Therefore, mastery of mathematics is absolutely necessary and mathematical concepts must be understood correctly. In Indonesia, students' ability to understand mathematics is still relatively low. From this, understanding of mathematical concepts needs to be improved again so that students clearly understand mathematical concepts. In order to improve understanding of mathematical concepts, various efforts were made. One of the efforts carried out by the author is a semantic web-based learning media system using concept maps in basic mathematical ontologies. This system will use ontology to build a system that will represent a mathematical concept as a domain of knowledge explicitly about other concepts related to previous concepts by giving meaning, properties, and relations so as to form a knowledge base. In this research, the writer uses methodological method to build the basic mathematical ontology and the system development will be done by prototyping method. The system built has 2 features, namely exploration and semantic search, with the aim that the existing knowledge in the system can be accessed systematically and according to user needs. To ensure that the system built can run as expected, system testing with black box testing has shown which features in the program run according to their functions and ontology evaluation using OntoQA on Schema Metrics carried out by measuring Relationship Richness (RR), Attribute Richness (AR), and Inheritance Richness (IR). In the evaluation of this ontology, it shows that the Relationship Richness (RR) value is 0.06; Attribute Richness (AR) value is 0.5; and the value of Inheritance Richness (IR) is 14.5.